Strategy of a top agriculture co-operative in the central planned economy. The differentiation of the organization in perspective social system theory. Issue 2 (3rd April 2019) - Šerá, Eva
ABSTRACT: The article examines differentiation of the agriculture co-operative JZD Slušovice which was one of the most efficient co-operatives in the centrally planned economy in Czechoslovakia in 80s. The purpose is to explain differentiation ways of the co-operative with the case production of computers as sideline production in the mentioned period. According to Luhmann's social system theory, the co-operative represents a social organized system differentiated from the environment defined as CZ economy. The theoretical concept decision premises including the concept the form of firm by D. Baecker are used for the analysis. The result of the analysis are decision premises specified as programs that show how a management decided on production strategy. It means distinctions between how organization self-observed and observed environment, and a way of observing, that is decision making on the strategy, differentiated the co-operative from environment. One of programs was the objective decision-making premise on what the product needs to be like to bring profit. This objective determined decision-making premises of condition programs, so decision-making on resources, which would help achieve such TNS PCs, the style of how to offer them to public so they would be accepted, and decisions on image to be created through the TNS PCs.